Our mom has cancer - Ackermann, Abigail (Atlanta, Ga. : American Cancer Society, 2001)
Two sisters, ages eleven and thirteen, describe what it was like for them when their mother was diagnosed with breast cancer and underwent surgery and chemotherapy
Keywords: Breast -- Cancer -- Juvenile literature; Breast -- Cancer; Cancer -- Patients; Diseases; Children's writings